Biotechnology of neglected and underutilized crops - Dutta Gupta, Sarmistha (Springer, 2013)
Almost 95% of the world food requirement is met by 30 plant species and there is a great need to expand plant genetic diversity. This book examines research achievements in neglected and underutilized crop biotechnology to help broaden crop diversity